Exploring smallholder farmers’ access and participation in the Home Grown School Feeding Programme in selected counties of Kenya - Kamau, Joyce; Okoyo, Collins; Kanyui, Tabitha; Mwandawiro, Charles; Singh, Samrat; Drake, Lesley (Frontiers in Public Health, 2025)
IntroductionSmallholder farmers (SHFs) produce 80% of the total agricultural output in Kenya. The Home Grown School Feeding Programme (HGSFP) was designed to address short-term hunger among primary school children from food-insecure households, enhancing access to primary education while providing a market to SHFs through local procurement of food for schools. This study investigated SHF access and participation in the HGSFP market and the uptake of a mobile phone platform (MPP) in HGSFP procurement in Tharaka Nithi, Kitui and Kilifi Counties of Kenya.MethodologyDescriptive cross-sectional study design was utilized and data were collected from SHFs, school teachers and farmer-based organizations (FBOs) within the schools’ locality using semi-structured questionnaires. A total of 378 SHFs, 92 FBOs and 70 school teachers were interviewed for the study. Data were analyzed using Stata version 16.ResultsThe study revealed that SHFs (22.8%) and FBOs (37.5%) gained access to HGSFP market and sold produce of maize (92.9%) and beans (91.4%). The main channel used by SHFs to sell produce to schools was through the FBOs (61.6%) amidst challenges of lack of surplus to sell (53.2%), low prices (50.9%) and poor transport infrastructure (23.6%). HGSFP schools purchased most of their food requirements from traders/brokers through manual tendering (65%). The uptake of the MPP for procurement of food by HGSFP schools and FBOs was embraced and promising and was rated as faster to use (76.8%) and more transparent in HGSFP procurement (44.6%).ConclusionThe study concluded that local procurement opportunities through FBOs were underutilized. We recommend more capacity-building support for SHFs and FBOs to increase their production and give them better opportunities to be key participants in the HGSFP market and other structured markets. The MPP should be adopted for the procurement of food for school meals for transparency and accountability. To maximize its benefits, it should be inclusive of all market players, especially traders/brokers and sufficient training should be provided to all stakeholders to participate fully in the HGSFP market.